Artikulasi Syarah Hadis dalam Bahasa Jawa: Studi tentang Kitab al-Azwād al-Muṣṭafawiyah Karya Bisri Mustofa - Kasan Bisri; Endang Supriadi; Rizqa Ahmadi (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Islamic teachings recorded in the hadith are closely related to the Arabic language and culture. This fact has become a challenge for Indonesian scholars to preach Islamic teachings in the archipelago. To ground the hadith, the archipelago scholars tried to articulate it in local languages, including Javanese. This is what Bisri Mustofa (1915-1978) did. This research attempts to examine how Bisri Mustofa articulated the commentaries of hadith (syarḥ al-ḥadīṡ) through Javanese in his work al-Azwād al-Muṣṭafawiyah. Specifically, this research tries to find the local context that appears in the book. By using the descriptive analysis method, this research concludes two findings. Firstly, Bisri articulates the syarah of hadith briefly and globally (ijmāli) in Javanese, which is easy to understand and comprehend. In several aspects, the syarah of hadith used the intertextual method, which links the hadith with the al-Qur'an and other related hadith (tanawwu 'al-aḥādiṡ). He also paid attention to the historicity of hadith by mentioning the reasons for the emergence of hadith (asbab al-wurūd al-ḥadīṡ). Secondly, the articulation of the syarah hadith is vibrant with the locality. Bisri does not hesitate to link the syarah hadith with local cultures such as selametan, kenduren, kondangan, and even the Javanese proverb (unen-unen). Bisri is also not awkward when he connects the explanation of the hadith with the socio-political conditions in Indonesia, such as the struggle through parliamentary seats, the Islamic Party in Indonesia, and the government's role in amar ma'ruf nahi munkar. Bisri's openness in accommodating local contexts gives its characteristics to the typology of syarah hadith in the archipelago through his work al-Azwād al-Muṣṭafawiyah.